Extremely Large Magnetic-Field-Effects on the Impedance Response of TiO(2) Quantum Dots - Mombrú, Dominique (Sci Rep, 2019)
Here, we report large magnetoresistance and magnetocapacitance response of undoped TiO(2) quantum dots weighting the contribution of both grain and grain boundaries by means of impedance spectroscopy. We also performed a complete characterization of the TiO(2) quantum dots (~5 nm) prepared by sol-gel via water vapor diffusion method, using X-ray diffraction, small angle X-ray scattering, transmission electron microscopy and Raman spectroscopy. In addition, we showed a complete theoretical study on the electronic properties of TiO(2) surface and subsurface oxygen and titanium vacancies to shed some light in their electronic and magnetic properties. Based in our study, we can conclude that the presence of defects, mainly at the grain boundary of these undoped TiO(2) quantum dots, could be responsible for the large positive magnetoresistance (+1200%) and negative magnetocapacitance (−115%) responses at low applied magnetic fields (1.8 kOe) and room temperature.